Identification of ribonucleotide reductase M2 as a potential target for pro-senescence therapy in epithelial ovarian cancer - Aird, Katherine M (Landes Bioscience, 2014)
Epithelial ovarian cancer (EOC) is the leading cause of gynecological-related cancer deaths in the United States. There is, therefore, an urgent need to develop novel therapeutic strategies for this devastating disease. Cellular senescence is a state of stable cell growth arrest that acts as an important tumor suppression mechanism. Ribonucleotide reductase M2 (RRM2) plays a key role in regulating the senescence-associated cell growth arrest by controlling biogenesis of 2'-deoxyribonucleoside 5′-triphosphates (dNTPs). The role of RRM2 in EOC remains poorly understood. Here we show that RRM2 is expressed at higher levels in EOCs compared with either normal ovarian surface epithelium (P < 0.001) or fallopian tube epithelium (P < 0.001). RRM2 expression significantly correlates with the expression of Ki67, a marker of cell proliferation (P < 0.001). Moreover, RRM2 expression positively correlates with tumor grade and stage, and high RRM2 expression independently predicts a shorter overall survival in EOC patients (P < 0.001). To delineate the functional role of RRM2 in EOC, we knocked down RRM2 expression in a panel of EOC cell lines. Knockdown of RRM2 expression inhibits the growth of human EOC cells. Mechanistically, RRM2 knockdown triggers cellular senescence in these cells. Notably, this correlates with the induction of the DNA damage response, a known mediator of cellular senescence. These data suggest that targeting RRM2 in EOCs by suppressing its activity is a novel pro-senescence therapeutic strategy that has the potential to improve survival of EOC patients.